2005
DOI: 10.1158/1078-0432.ccr-04-0548
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile Associated with Response to Doxorubicin-Based Therapy in Breast Cancer

Abstract: A trio of genes might potentially distinguish doxorubicin-responsive from nonresponsive tumors, but further validation by a larger number of samples is still needed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
109
0
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 31 publications
1
109
0
13
Order By: Relevance
“…A previous study showed that CLPTM1L was an up-regulated transcript in cisplatin-resistant ovarian tumor cell lines (Yamamoto et al, 2001). Interestingly, it was found that the CLPTM1 homolog was expressed at higher levels in doxorubicin-resistant breast cancer (Folgueira et al, 2005). Recently, a genetic variant within the CLPTM1L gene (rs402710) was shown to be associated with the accumulation of DNA adducts in lung tissue adjacent to tumors (Zienolddiny et al, 2009).…”
Section: A B Discussionmentioning
confidence: 99%
“…A previous study showed that CLPTM1L was an up-regulated transcript in cisplatin-resistant ovarian tumor cell lines (Yamamoto et al, 2001). Interestingly, it was found that the CLPTM1 homolog was expressed at higher levels in doxorubicin-resistant breast cancer (Folgueira et al, 2005). Recently, a genetic variant within the CLPTM1L gene (rs402710) was shown to be associated with the accumulation of DNA adducts in lung tissue adjacent to tumors (Zienolddiny et al, 2009).…”
Section: A B Discussionmentioning
confidence: 99%
“…These signatures comprise known signatures such as the genomic grade index as well as several new classifiers [25][26][27][28][29][30][31][32][33][34][35][36][37]. Additional data to support the predictive potential for the 70-gene assay comes from the neoadjuvant study of Straver et al [38].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 PBEF1 overexpression has also been shown to predict poor response to doxorubicin-based primary chemotherapy in breast cancer patients. 18 Further, NAD + , the final product of salvage pathway catalyzed by NAmPRTase, is an essential coenzyme that is also used as a substrate in several biochemical reactions, such as those catalyzed by poly (ADP-ribose) polymerase (PARP1), sirtuins and ADP-ribosyl cyclase. 19 In particular, NAmPRTase, the rate-limiting component in the NAD + biosynthesis pathway, regulates the function of the Sir2 ortholog, Sirt1, in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%